Rural houses infestation by Triatoma infestans in northwestern Argentina: Vector control in a high spatial heterogeneous infestation area - Cavallo, María José (2018)
Triatoma infestans (Hemiptera: Reduviidae) is a vector of the Trypanosoma cruzi parasite, causative agent of Chagas disease. During the last decade, vector control activities have been systematically carried out in northwestern Argentina, an endemic region for this disease. The general aim of this study to evaluate was spatio-temporal variation of infestation by T. infestans in rural communities of Los Llanos in La Rioja province. We estimated house infestation using two sampling methods: passive and active. Passive collection was conducted with community participation collecting triatomines. Six passive collections were carried out in 397 houses during the warm season between 2014 and 2017. Active collection of T. infestans was thoroughly performed by trained staff for 60 minutes and was carried out once in March 2016. The estimate of intradomestic infestation did not show significant differences between both collection methods (p = 0.39). However, passive collection method had lower sensitivity than active collection method for the estimation of peridomestic infestation and intradomestic colonization (PDI: p< 0.01; ID colonization: p< 0.01). The results obtained with passive collection methods showed that the infestation in the study area was spatially heterogeneous and temporally variable. Intradomiciliary infestation decreased over time (14.4% to 7.9%, p<0.05) although the effect of the chemical treatment application was not associated with the infestation level of T. infestans (p = 0.15) and the Departments had a different response each year (p<0.01). A high infestation cluster was located in the south of our study area during 2016–2017. The vector presence in the houses confirms the importance of to improve entomological surveillance programs. The search for triatomines carried out by the inhabitants might be a useful method to complement the activities of vector control programs in isolated and rural areas.